ANALISIS IMPLEMENTASI KEBIJAKAN PERLINDUNGAN PEREMPUAN DAN ANAK PADA PENGEMBANGAN GERAKAN PERLINDUNGAN ANAK TERPADU BERBASIS MASYARAKAT (PATBM) DI KABUPATEN BURU - Oclaila Sulaiman; Tehubijuluw Zacharias (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
Violence that often occurs against women and children in Buru Regency is increasingevery year. The Government of Buru Regency responded to this by issuing a policy in theform of Regional Regulation Number 13 of 2015. However, the issuance of this policy didnot succeed in reducing the number of increases in violence. Therefore, the Government ofBuru Regency began to issue a policy in the form of Regent's Instruction Number 266/79concerning the Establishment of Community-Based Integrated Child Protection (PATBM).This study aims to analyze the Implementation of the Protection Policy for Women andChildren in the Development of the PATBM Movement and the factors that influence it. The method used in this study is a qualitative method with descriptive research. The mainfocus that will be examined in this research are: (1) the implementation of women andchildren protection policies in PATBM (2) the factors that play a role in influencing theimplementation of women and children protection policies in PATBM. The indicators usedto measure policy implementation use Charles Jones theory while the indicators used tomeasure factors use Edwards III theory. This research uses triangulation analysistechnique. The results obtained from this study are that the policy of protecting women andchildren in PATBM has not been implemented properly. Out of the 11 PATBMs formed,only 3 PATBMs carry out their functions properly. However, the 3 PATBMs were also notaccompanied by an sufficient budget. The suggestions recommended in this study are thatlocal government support is needed to provide confirmation for villages that do not formPATBM by providing sanctions and support from the village government to be able tobuild a stronger commitment in providing PATBM budgets. The implication of thisresearch is that PATBM has an influence as the implementer of the protection policy. Theimplementation of protection policies by PATBM is carried out from the complaintregistration process to integrated services using a reciprocal system